Kwestia zła w psychiatrii - Jacek Bomba (Jesuit University Ignatianum in Krakow, 2017)
Psychiatry, being a discipline of applied knowledge, rather doesnotdecideon what is wrong. It refers to the arrangements madeby the basic sciences on which it is based. Nevertheless, psychiatryhasthetaskofrefrainingfromjudgingmanmorally,on the basis of his deeds if, on the basis of clinical knowledge it judgesthemassymptomsofmentaldisorder.Thispostulatearises from the assumption that disorder is not man's free choice, atthesametimelimitinghisabilitytodifferentiatebetweengood and evil, as well as the possibility of influencing his own behaviour. In the face of constant changes in the understanding of the essence of mental disorders and the rules of therapeutic proceedings, contemporary psychiatrist every single time has to make decisions judging the connections between man's behaviour and the condition of his mental health. On one hand, it resultsfromthehistoryofpsychiatry,whichobservedmentalhealth disordersinsituationspreviouslyperceivedasevil.Ontheother hand, it results from using psychiatry in solving social and political problems, especially in totalitarian systems. Contemporaryprogressofdevelopmentalpsychologyanddevelopmentalneurophysiologyforcesustopaycloserattentiontothe influence of parental care and education on the possibility of the developmentofmentalhealthdisorders.Abandoningtheprevention of mental disorders where, in the light of empirical research resultsitseemspossible,appearsasthesourceoffutureevil. Contemporary psychiatry, focusing on the participation of genetic information and the epigenetic nature of development canbealsofoundinatrap of determinism, limiting the meaning of man's individual influence on his personal development, including using the possibility of maintaining mental health.